Mediating Role of Risk Perception and Environmental Quality on the Relationship Between Risk Knowledge and Traveler’s Intention in COVID-19 - Yang, Dongxu; Fang, Ning; Ramirez-Asis, Edwin; Alashker, Yasser; Abourehab, Mohammed A. S.; Zhang, Kun (Frontiers in Environmental Science, 2022)
The recent outbreak of epidemic disease (COVID-19) has dramatically changed the socio-economic and environmental dynamics of the world. In particular, it affects human movement, travel intentions, and ambient air pollution amid rising stringency measures. Therefore, this study examines the influence of tourism knowledge, environmental vulnerability, and risk knowledge on travelers’ intentions in China’s tourism industry during COVID-19. To address the study objectives, an online survey questionnaire was created, through which a valid sample of 402 respondents was achieved. The direct and indirect relationship between variables was tested through structural equation modeling, the outcomes confirm that both tourism knowledge and risk knowledge in terms of COVID-19 significantly and negatively define the travelers’ intention toward tourism. Moreover, environmental vulnerability moderately affected tourism behavior and augmented with COVID-19 stringency disclosures. The mediating effect of risk perception and attitude towards the relationship between exogenous and endogenous constructs was tested. It shows a significant mediating impact of risk perception, environmental hazards and attitude towards risk on the nexus between tourism knowledge and travelers’ intention. The study offers valuable recommendations for policymakers to understand tourist intentions and climate vulnerability.